A Non-Invasive Tool of Cholesterol Level Measurement Prototype Using TCRT 5000 Sensor To Reduce Medical Waste - Shofani, Maya; Hardiyanto , Firman (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
In this study, we develop non non-invasive tool for cholesterol level measurement using the TCRT 5000 sensor. The tool used Arduino as an electronic prototype and the TCRT 5000 sensor as a detector. The study employs the R&D (Research and Development) design, progressing through the stages of planning, development, and testing of the tool. The development of a non-invasive cholesterol tool can be an innovative tool that is easy, cheap, reduces medical waste, and is not painful (invasive). This development can also help reduce the buildup of non-invasive biodegradable medical waste. The accuracy of the tool developed by the researcher for measuring 14 samples yielded an average error value of 2.42%, with a tool accuracy of 97.58%.